Innovating for the Global South : Towards an Inclusive Innovation Agenda - DILIP SOMAN, JANICE GROSS STEIN (University of Toronto Press, 2014)
Basic sanitation, access to clean water, and hygiene are all things that many of us living in the First World take for granted. Consider, however, that according to United Nations (UN) estimates, nearly 2.5 billion people, or about 40 per cent of the worldâ€™s population, do not have access to basic sanitation and clean drinking water. Access to sanitation is a global challenge, and the implications of such limited access are manifold, particularly for those who are very poor. We know, for instance, that infant mortality rates in the developing world can be drastically reduced and child development enhanced if children have access to basic sanitation. We also know that more than 2 million people die each year because of diarrheal disease, which is connected to poor sanitation. Humans suffer, and productivity suffers as well. Estimates show that economic output equivalent to over 5 billion productive days (working days) is lost each year because of diarrhea-related disease; the lack of proper sanitation constrains economic development. The images of open defecation, flooded pit latrines, and contaminated water remind one of the images of Dickensian London. The tragedy, of course, is that Dickensâ€™s England is of the nineteenth century. According to a recent survey conducted by the British Medical Journal, the â€œprovision of clean water and sewage disposalâ€ was found to have had the greatest